Effect of open phase condition on asynchronous machine - Skala, Bohumil; Kindl, Vladimir; Frivaldsky, Michal; Sobotka, Lukas; Zavrel, Martin (Electrical engineering, 2025)
This paper investigates the influence of an asymmetrical power supply on induction machines, focusing on key parameters such as temperature rise, torque, efficiency, and power factor. Various three-phase voltage asymmetries are examined to determine their impact on the magnitude of the negative-sequence voltage component. The study further explores how a drop in phase voltage leads to a significant negative component, the effect of phasor rotation from its ideal position, and the number of phases subject to voltage drops or phase shift errors. A voltage synthesis approach is employed to analyse the roles of the positive and negative components, with one component held constant to evaluate the resulting changes in power factor, efficiency, and torque. In addition, a dynamic thermal model is implemented to assess the machine’s temperature rise under load conditions.